Non-adherence to growth monitoring and promotion sessions amongst caregivers of children under 5 years in Polokwane Municipality, Limpopo province - Mabitsela H. Mphasha; Matjie Rapetsoa; Nkhaviso Mathebula; Kamogelo Makua; Sanele Mazibuko (South African Family Practice)
Background: Child growth is crucial for nutritional and health status; poor growth may result in stunting. South Africa experiences a high prevalence of stunting, micronutrient deficiencies and late identification of growth faltering. Non-adherence to growth monitoring and promotion (GMP) sessions remains a challenge and caregivers contribute to non-adherence. Therefore, this study explores factors affecting the non-adherence of GMP services.